A logistics optimization study for Garden City Co-op, Inc. - Kempke, Michael (Kansas State University, 2013)
Garden City Co-op, Inc. is a farm cooperative in Southwest Kansas. It provides marketing and storage of grain, fertilizer, crop protection products, seed, and petroleum to both member and non-member accounts. The cooperative also operates a transportation company called Western Transport. Western Transport provides transportation of anhydrous ammonia (NH3), liquid fertilizer (32-0-0 or 10-34-0), diesel, gasoline, and propane utilizing semi-tractors and trailers to Garden City Co-op, Inc. as well as to other agribusinesses in the region. The purpose of this thesis is to integrate and optimize the supply chain strategies for the cooperative’s fertilizer and petroleum products as it relates to storage and transportation of those commodities. Utilizing the framework of an aggregate production plan, a model is constructed to minimize costs associated with inventory holding, net storage asset depreciation after tax savings, net transportation asset depreciation after tax savings, labor, operations, and freight. By varying the quantities of petroleum and fertilizer the cooperative purchases, sells, and stores each month over a one-year period, an optimum mix of storage and transportation assets is determined. Two different demand scenarios are evaluated that relate to demand during a drought year versus demand during a non-drought year. Also, different model scenarios include varying beginning period inventory and ending period inventory to stress transportation assets versus storage assets. The model is optimized using a genetic algorithm solver in the software program Evolver produced by Palisade Corporation. Results of the optimization provided two feasible strategies for the cooperative. By continuing services to non-member accounts, there was a greater investment placed on transportation. Investments included additional trucks, NH3 trailers, petroleum trailers, and drivers. The strategy favored a just-in-time inventory approach versus inventory smoothing with storage. When discontinuing services to non-member accounts, investment between storage and transportation assets were relatively equal. The model favored a reduction in NH3 trailers, liquid fertilizer trailers, trucks, and drivers. However, additional storage was necessary as well as petroleum trailers. The scenario favored an inventory smoothing approach across the model year.
Keywords: Logistics; Cooperative; Optimization; Supply chain